The Correlation Among Three Different Dietary Intake Methods in Cognitively Normal Healthy Older Adults. (29th May 2020) - Alhayek, Sibelle; Taylor, Matthew; Spaeth, Kendra; Choi, In-Young; Lee, Phil; Sullivan, Debra
Abstract: Objectives: This study's purpose was to investigate the correlation among three dietary intake methods: 24-hour recall, 7-day food record, and the National Cancer Institute's Dietary History Questionnaire (DHQ)-II in older adults. Methods: Dietary intake was collected from 60 cognitively normal, healthy older adults aged between 60–85 years using three 24-hour recalls (3–24HR), a 7-day food record (7D), and a food frequency questionnaire (DHQII). The 24-HR and 7D were entered in the Nutrient Data System for Research (NDS-R version 2012) and DHQII was exported to Diet*Calc software for nutrient analysis. We determined the correlation among the 3 dietary intake methods by Pearson correlation. Statistical analyses were performed using SPSS (v25, IBM) with significance of P ≤ 0.05. Results: Correlation of energy, macronutrients and 22 micronutrients from the three methods were assessed. For energy and macronutrients, there was a significant correlation among the three dietary intake methods, except for fat between DHQII and 3–24HR (r2 = 0.24; P = 0.06). For energy, correlations were: DHQII and 3–24HR (r2 = 0.30; P < 0.05), DHQII and 7D (r2 = 0.43; P < 0.01), 3–24HR and 7D (r2 = 0.58; P < 0.01). We observed similar correlations with proteins and carbohydrates. All micronutrients were correlated between 3–24HR and 7D (r2 range:0.30–0.85), 21 micronutrients were correlated between DHQII and 7D (r2 range:0.11–0.85), and 17 micronutrients were correlated between DHQII and 3–24HR (r2 range:0.01–0.75). Conclusions: All three methods are adequate for dietary intake assessment in cognitively normal older adults. The 24-hour recalls were strongly correlated with the gold standard (7D). 24-hour recalls may provide sufficient dietary intake information with less participant burden. Funding Sources: This study is supported by funding from the Dairy Research Institute (I-YC). The Hoglund Brain Imaging Center is supported by grants from the NIH (C76 HF00201, P30 HD002528, S10 RR29577, UL1 TR000001, and P30AG035982) and the Hoglund Family Foundation.